Chip-scale GaN integration. (March 2020) - Li, K.H.; Fu, W.Y.; Choi, H.W.
Abstract: Blue LEDs and HEMTs based on III-Nitride have been flourishing commercially across the globe, thanks largely to breakthroughs in the material quality of the wide-bandgap compound semiconductor back in the 1990s. The realizations of white-light LEDs, blu-ray systems, and lately efficient compact chargers have drastically changed the way we live and have contributed tremendously to global energy saving efforts. The maturity and diversity of modern discrete GaN-based devices open up opportunities for an integrated GaN platform with extended functionalities and applications. In this review paper, we present an overview of the monolithic and heterogeneous integration of GaN devices and components. Various methods for the integration of electronic, optoelectronic, and optical components based on GaN are discussed.